Strengthening the role of Village-Owned Enterprises (BUMDes) in South Sumatra through Islamic social entrepreneurship ‎ - Fahmi, Rizqi Anfanni; Panorama, Maya (Universitas Islam Indonesia, 2025)
IntroductionVillage-Owned Enterprises play a vital role in rural development in Indonesia. However, in South Sumatra, the majority of these enterprises face persistent challenges related to governance, financial sustainability, and community engagement. Despite substantial government funding, only a small fraction of Village-Owned Enterprises operate effectively. Given the region’s predominantly Muslim population, there is significant potential to enhance Village-Owned Enterprises through faith-driven economic models grounded in Islamic principles.ObjectivesThis study aims to explore how the integration of Islamic Social Entrepreneurship can strengthen Village-Owned Enterprises in South Sumatra. It examines the alignment between Islamic ethical values and key factors that determine enterprise success, such as government support, professional management, and active community participation.MethodThe study adopts a qualitative library research method, relying on content analysis of peer-reviewed literature, government reports, and empirical case studies published between 2014 and 2024. The data were organized into thematic categories to assess how Islamic principles—including economic justice, religious-based ethics, and Islamic philanthropy—can be applied to improve the performance and sustainability of Village-Owned Enterprises.ResultsThe findings indicate that Islamic Social Entrepreneurship provides a holistic framework for transforming Village-Owned Enterprises into transparent, accountable, and socially impactful institutions. The application of values such as trustworthiness, economic jihad, and community-oriented governance enhances public trust and operational resilience. Islamic financial instruments, including zakat and waqf, offer viable alternatives to conventional funding, reducing dependency on external aid. Moreover, real-world case studies have demonstrated that integrating Islamic values into enterprise governance results in higher community participation, more efficient management, and stronger economic outcomes.ImplicationsThis study underscores the strategic potential of embedding Islamic ethics in rural enterprise development. Strengthening partnerships between Village-Owned Enterprises, Islamic philanthropic organizations, and local governments can build inclusive business ecosystems. This approach not only promotes poverty alleviation but also enhances financial independence and community empowerment in Muslim-majority regions.Originality/NoveltyThis research fills a critical gap by proposing Islamic Social Entrepreneurship as a culturally relevant and scalable model for improving Village-Owned Enterprises. Unlike prior studies, which focused solely on economic or managerial dimensions, this study introduces a religiously grounded governance framework that integrates Islamic values with local potential, offering a novel contribution to both entrepreneurship and development studies.